Counseling Students’ Attitudes toward Statistics - García-Martínez, José Antonio (2015)
This paper presents the findings of a study aimed at analyzing the attitudes toward Statistics of a sample of 223 Counseling students, as well as identifying possible attitude differences by socio-demographic characteristics and prior training in Statistics.  Based on a cross-sectional design, data was collected using SATS (Survey of Attitudes toward Statistics), which includes four components (affective, cognitive competence, value and difficulty), as well as several questions on the participants’ socio-demographic characteristics and prior Statistics training.  Results show a positive attitude toward Statistics among students, both overall and by component. No significant attitude differences were found by socio-demographic characteristics. On the contrary, significant differences were detected according to prior Statistics training, with trained students showing more positive attitudes than untrained ones.  Obtained findings confirm the relevance of including a course in Descriptive Statistics as part of the training of Counseling professionals, as well as the need to analyze the statistical contents included in other courses of the curriculum.